Effectiveness of Video Assisted Teaching Programme (VATP) on Prevention and Management of Child Abuse Among Mothers of Children in Selected Rural Area, Mangalore - Malla, Chandani; Rai, Dipa Khaling; Poudel, Pramila; Hodlur, Shridhar (Med Phoenix, 2018)
Background: Every child has a right to a safe childhood and a life free from violence. The experience of child abuse and neglect infringe upon that right. 1 Health education will improve the knowledge level of the mothers so that proper awareness can be built towards the prevention and management of child abuse. The overall aim of the study was to assess the effectiveness of video assisted teaching programme on prevention and management of child abuse among mothers of children. Method: Pre-experimental approach with one group pre-test - post-test design was adopted to accomplish the objectives. Non probability Purposive sampling technique was used to select the sample of 100 mothers and semi-structured knowledge questionnaire was developed to assess the knowledge level. Results: The findings of the study revealed that most (57%) of the mothers had moderate knowledge and majority (43%) of the mothers had inadequate knowledge regarding prevention and management of child abuse. After administration of video assisted teaching programme (VATP), the posttest knowledge score (25.28± 2.025) was higher than the pretest knowledge score (11.03± 2.213). The calculated ‘t’ value in knowledge (48.668; p< 0.05) was greater than the table value (1.98) at 0.05 level of significance. Conclusions: The present study revealed that the mothers have lack of knowledge on prevention and management of child abuse and the overall findings of the study proved that there was a highly significant increase in the knowledge of the mothers on prevention and management of child abuse following the administration of the VATP. Therefore it was concluded that the VATP was highly effective in improving the knowledge of the mothers on prevention and management of child abuse. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 66-70